2008
DOI: 10.1002/ange.200802223
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of an Aspartate‐Based Epoxidation Catalyst with Amide‐to‐Alkene Peptidomimetic Catalyst Analogues

Abstract: Geschickt ausgetauscht: Der Ersatz einer Amidfunktion durch Alken‐ und Fluoralkengruppen führt zu einer neuen Klasse von peptidischen Epoxidierungskatalysatoren (siehe Schema; Boc=tert‐Butoxycarbonyl). Das unterschiedliche Reaktionsverhalten der isosteren Peptide gewährt Einblicke in ihren Katalysemechanismus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 53 publications
0
13
0
2
Order By: Relevance
“…The advantage of using a DG lies in the ability to functionalize nonpolar bonds (such as in alkenes) while maintaining beneficial polar interactions between the substrate and chiral source; however, DGs have rarely been used in organocatalysis. In this context, the Miller research group reported the epoxidation reaction of allylic alcohols, using an amino acid catalyst capable of hydrogen bonding with the alcohol DG, and conducted elegant studies delineating the importance of hydrogen-bonding interactions for this and related systems (7)(8)(9) (Fig. 1).…”
mentioning
confidence: 99%
“…The advantage of using a DG lies in the ability to functionalize nonpolar bonds (such as in alkenes) while maintaining beneficial polar interactions between the substrate and chiral source; however, DGs have rarely been used in organocatalysis. In this context, the Miller research group reported the epoxidation reaction of allylic alcohols, using an amino acid catalyst capable of hydrogen bonding with the alcohol DG, and conducted elegant studies delineating the importance of hydrogen-bonding interactions for this and related systems (7)(8)(9) (Fig. 1).…”
mentioning
confidence: 99%
“…Coupled with its electronegativity, fluorine’s small size has made it an attractive choice for isosteric substitutions of hydrogen or other functional groups, especially those containing oxygen. In this regard, fluoroalkene isosteres of peptide amide bonds have become increasingly prevalent as structural and mechanistic probes in both biological5 and chemical studies 6…”
mentioning
confidence: 99%
“…Given our interest in fluoroolefins as mechanistic probes,6 we sought to expand the methodology for Au-catalyzed nucleophilic fluorination of alkynes by developing new avenues for regiocontrol that would expand both the utility and substrate scope of the reaction. Specifically, we envisioned a classical heteroatom-directed reaction that might confer a high degree of selectivity for a broad range of substrates 11.…”
mentioning
confidence: 99%
“…[18] Es wird angenommen, dass Wasserstoffbrücken zwischen dem Katalysator und dem Alken für einen hohen Grad an Stereoinduktion entscheidend sind, da Substrate ohne ersichtliche Mçglichkeiten für Wasserstoffbrücken fast keine Enantioselektivität zeigten. [18] Es wird angenommen, dass Wasserstoffbrücken zwischen dem Katalysator und dem Alken für einen hohen Grad an Stereoinduktion entscheidend sind, da Substrate ohne ersichtliche Mçglichkeiten für Wasserstoffbrücken fast keine Enantioselektivität zeigten.…”
Section: Elektrophile Epoxidierung Von Alkenen Und Mechanistische Betunclassified
“…Der Mechanismus der tripeptidkatalysierten asymmetrischen Epoxidierung wird immer noch erforscht. [18] [19] Dieses Verfahren wurde später erfolgreich genutzt, um das schwierige Problem der regio-und enantioselektiven Epoxidierung von Polyenen, wie des Sesquiterpens Farnesol und von verwandten Verbindungen, anzugehen (Schema 6). [20] Unter Verwendung des Katalysators 20 wurden eine nahezu perfekte Regioselektivität bezüglich der Doppelbindung neben der allylischen OH-Gruppe und eine hohe Enantioselektivität von 87 % ee erzielt.…”
Section: Epoxidierung Von Elektronenarmen Ab-ungesättigten Aldehydenunclassified